Ethylene polymerization with a nickel diimine catalyst covalently anchored on spherical ZSM-5. (16th February 2017) - Favero, C.; Lima, D. W.; de Souza, R. F.; Bernardo-Gusmão, K.
Abstract : Late transition catalysts play an important role in the catalytic conversion of olefins into polymers with different microstructures. Abstract : Late transition catalysts play an important role in the catalytic conversion of olefins into polymers with different microstructures. Homogeneous nickel-based catalysts are known for their outstanding activity and low metal cost. However, the homogeneous nature of the catalysts is a major disadvantage and does not fit current heterogeneous processes. Some advantages that justify the heterogenization of these catalysts include the ability to perform polymerization reactions using small amounts of solvent or no solvent, polymer growth control and decades of industrial improvements. In this study, we propose the use of a spherical ZSM-5 zeolite as a support for a nickel diimine catalyst, with the expectation that morphological replication of the support would be observed in an ethylene polymerization reaction. First, the zeolite was pre-treated with trimethylaluminium (TMA), followed by the addition of the catalyst (dibromo-bis(4-amino-2, 3, 5, 6-tetramethylphenylimino)-acenaphtenenickel[ii ]). The covalently anchored catalyst was used under different conditions and compared with the homogeneous catalyst. During polymerization with TMA at 60 °C, the productivity reached nearly 1000 kg PE mol(Ni) −1 h −1 for both catalysts. When the experiments were performed at 10 °C, the productivity increased to 4408 and to 3764 kg PE mol(Ni) −1 h −1 for the homogeneous and heterogenized catalysts, respectively. Methylaluminoxane (MAO) was also used and further improved the productivity to 14 000 kg PE mol(Ni) −1 h −1 for both systems. Morphological replication was observed, especially in the first stages of the polymerization process. The zeolite showed good influence on morphological control due to the morphological replication and we achieved a highly active heterogenized catalyst compared to the homogeneous analogue.